Answer: √(f^2 - 2f + 1) = a
Step-by-step explanation:
We have that:
f^2+g^4-2f+1 = a^2+(g^2)^2
And we want to find the value of a, so we should isolate it.
f^2 + g^4 - 2f + 1 = a^2 + g^(2*2) = a^2 + g^4
where i used that (x^y)^z = x^(y*z)
We can remove the term g^4 in both sides of the equation and get:
f^2 - 2f + 1 = a^2
now we can apply the square rooth to both sides and get
√(f^2 - 2f + 1) = a
So we just found the value of a.
Answer:
2369.86
Step-by-step explanation:
f(36)=3700(1−0.06) ^36/5
2369.857704098921
Units. I believe have an amazing day you amazing person
Answer:
2.5 yards
Step-by-step explanation:
75÷30=2.5 yards
Hope this helps!